Konsep Pendidikan Multikultural Di Universitas Yudharta Pasuruan - Akhmad Sirojuddin (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2016)
Departing from a background of this research is the existence of various ethnic, tribal, and culture in Indonesia which is lifted into an ideology at the university Yudharta Pasuruan. Diversity becomes a social force to build the nation and this theory also becomes the vision of Yudharta University Mission which stands as education development program in Ngalah Pondok Pesantren Foundation. Conflict occurring in some places is a picture of how diversity of diversity can create violence and loss. Therefore, multicultural education is important to develop. Yudharta University, which is the only University that plotted as The Multicultural University and the largest campus in Pasuruan responded to this challenge in accordance with the ideology of caregivers who washatiyah and democratic. This study shows that the implementation of multicultural education at Yudharta University is going well. The university applies the concept of multicultural education by: (a) Creating MoUs with campus religious lintasa, some social institutions, social groups, banks, and others. (b) Opens the opportunity to learn from various religions, cultures, ideologies, races and sexes or discriminates Gander (c) Creates a rich curriculum design with multiculturalism, providing opportunities for self-exploitation with student center activities such as BEM, UKM, Traning and edu Entrepreneurs, scouts, mountaineers and others. In terms of strategies to enrich the value of multiculturalism University Yudharta Pasuruan put this subject into the learning process and become a reference policy stakeholders to the ideals of the institution that has been in.